Taking a Closer Look at Communication Strategy and its Pedagogical Implication in EFL Class - Muhammad Sukirlan (International Conference on Education and Language (ICEL), 2013)
The primary goal of English Language Teaching (ELT) is to develop the students’ communicative competence through which the students are expected to able to communicate messages in varieties of communicative situations both in spoken and in written forms. There are five copmponents of communicative competence, namely linguistic, sociolinguistic, discourse, actional, and strategic competences. One of theelements of strategic competence is the students’ use of communication strategies which will be the focus of this article.Communication strategies refer to the strategies used by the speaker to cope with the communication problems as the results of the gap between the speaker’s available linguistic knowledge and the messagehe/she intends to deliver. Therefore this article puts emphasis on the implementation of communication strategies in the classroom to support the achievement of students’ communicative competence. In particular, this article deals with communicative competence, definition of communication stragegy, taxonomy of communication strategy, teachingcommunicationstrategies, and teachingand learning activities in the class